Read the Silence: Well-Timed Recommendation via Admixture Marked Point Processes - Kim, Hideaki; Iwata, Tomoharu; Fujiwara, Yasuhiro; Ueda, Naonori (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
Everything has its time, which is also true in the point-of-interest (POI) recommendation task. A truly intelligent recommender system, even if you don't visit any sites or remain silent, should draw hints of your next destination from the ``silence", and revise its recommendations as needed. In this paper, we construct a well-timed POI recommender system that updates its recommendations in accordance with the silence, the temporal period in which no visits are made. To achieve this, we propose a novel probabilistic model to predict the joint probabilities of the user visiting POIs and their time-points, by using the admixture or mixed-membership structure to extend marked point processes. With the admixture structure, the proposed model obtains a low dimensional representation for each user, leading to robust recommendation against sparse observations. We also develop an efficient and easy-to-implement estimation algorithm for the proposed model based on collapsed Gibbs and slice sampling. We apply the proposed model to synthetic and real-world check-in data, and show that it performs well in the well-timed recommendation task.